Antinociceptive effect of plant-based natural products in chemotherapy-induced peripheral neuropathies: A systematic review - Santos, Wagner Barbosa Da Rocha; Guimarães, Juliana Oliveira; Pina, Lícia Tairiny Santos; Serafini, Mairim Russo; Guimarães, Adriana Gibara (Frontiers in Pharmacology, 2022)
Chemotherapy-induced peripheral neuropathy (CIPN) is one of the most prevalent and difficult-to-treat symptoms in cancer patients. For this reason, the explore for unused helpful choices able of filling these impediments is essential. Natural products from plants stand out as a valuable source of therapeutic agents, being options for the treatment of this growing public health problem. Therefore, the objective of this study was to report the effects of natural products from plants and the mechanisms of action involved in the reduction of neuropathy caused by chemotherapy. The search was performed in PubMed, Scopus and Web of Science in March/2021. Two reviewers independently selected the articles and extracted data on characteristics, methods, study results and methodological quality (SYRCLE). Twenty-two studies were selected, describing the potential effect of 22 different phytochemicals in the treatment of CIPN, with emphasis on terpenes, flavonoids and alkaloids. The effect of these compounds was demonstrated in different experimental protocols, with several action targets being proposed, such as modulation of inflammatory mediators and reduction of oxidative stress. The studies demonstrated a predominance of the risk of uncertain bias for randomization, baseline characteristics and concealment of the experimental groups. Our findings suggest a potential antinociceptive effect of natural products from plants on CIPN, probably acting in several places of action, being strategic for the development of new therapeutic options for this multifactorial condition.